Detection of resistance genes (gyrA,qepA,drf1,drf17) for E.coli in Iraqi aquatic environment (Baghdad Science Journal, 2024)
The control of water represents the safe key for fair and optimal use to protect water resources due to human activities, including untreated wastewater, which is considered a carrier of a large number of antibiotic-resistant bacterial species. This study aimed to investigate the prevalence of antibiotic-resistance to E. coli in Tigris River by the presence of resistance genes for aminoglycoside(qepA( ,quinolone (gyrA), and sulfa drugs( dfr1 ,dfr17) due to the frequent use of antibiotics and their release into wastewater of hospitals. Samples were collected from three sites on Tigris River: S1( station wastewater in Adhamiya), S2 (station wastewater in Baghdad Medical city hospital), S3 (station wastewater in Abu Nuwas) from February-July 2021. Out of 67 isolates of bacteria, only 40 isolates of E. coli were detected by Vitek2. The antibiotic-resistance was estimated by the disk diffusion method. All E.coli isolates were tested against 6 antibiotics. The results showed the high resistance antibiotic of E. coli against Ceftazidime 70%, with intermediate resistance to Cefotaxime 47.5%, and low resistance to the sulfa drugs as Trimethoprim 27.5% and quinolones antibiotics as ciprofloxacin 17.5%, aminoglycosides as Amikacin and Gentamycin 5% and 7.5%. Moreover, the results revealed that gyrA gene was detected in 4 isolates (10%) while drf1 and drf17 genes were in 2 isolates of each gene (5%).Whereas qepA gene has not appeared in isolates. In conclusion, the isolates of E.coli from the Tigris River showed low resistance to sulfa drugs and quinolones , aminoglycosides. The resistance genes (gyrA,drf1,drf17) were detected in a few isolates which may be explained by the horizontal transfer of plasmids that carried genes and their distribution among the family  Enterobacteriaceae.